Epidemiology and mortality of liver abscess in end-stage renal disease dialysis patients: Taiwan national cohort study. - Chon-Seng Hong (Public Library of Science (PLoS), 2014)
Background and objectives To determine the incidence rates and mortality of liver abscess in ESRD patients on dialysis. Design setting participants & measurements Using Taiwan's National Health Insurance Research Database, we collected data from all ESRD patients who initiated dialysis between 2000 and 2006. Patients were followed until death, end of dialysis, or December 31, 2008. Predictors of liver abscess and mortality were identified using Cox models. Results Of the 53,249 incident dialysis patients identified, 447 were diagnosed as having liver abscesses during the follow-up period (224/100,000 person-years). The cumulative incidence rate of liver abscess was 0.3%, 1.1%, and 1.5% at 1 year, 5 years, and 7 years, respectively. Elderly patients and patients on peritoneal dialysis had higher incidence rates. The baseline comorbidities of diabetes mellitus, polycystic kidney disease, malignancy, chronic liver disease, biliary tract disease, or alcoholism predicted development of liver abscess. Overall in-hospital mortality was 10.1%. Conclusions The incidence of liver abscess is high among ESRD dialysis patients. In addition to the well known risk factors of liver abscess, two other important risk factors, peritoneal dialysis and polycystic kidney disease, were found to predict liver abscess in ESRD dialysis patients.